Mass spectrometry-based metabolomics reveal the effects and potential mechanism of isochlorogenic acid A in MC3T3-E1 cells - Zhu, Lian; Xie, Liu; Wang, Ziming; Li, Kai-Lin; Cai, Wei (Frontiers in Molecular Biosciences, 2025)
IntroductionThe bioactive compound 3,5-DiCQA, derived from Duhaldea nervosa, has been traditionally utilized in folk remedies for bone fractures and osteoporosis. However, its therapeutic mechanisms remain unclear.MethodsWe employed UHPLC-Q Exactive Orbitrap MS-based cell metabolomics to investigate the molecular mechanisms of 3,5-DiCQA in MC3T3-E1 cells. Cell proliferation was assessed via MTT assay, differentiation by alkaline phosphatase (ALP) activity, and mineralization through alizarin red staining and cetylpyridinium chloride quantification. Metabolomic profiling compared drug-treated and control groups.ResultsResults from MTT assays demonstrated that 3,5-DiCQA significantly promoted cell proliferation at 100 μM. Alkaline phosphatase (ALP) assays and alizarin red staining revealed enhanced osteoblast differentiation and mineralization, respectively. Calcification deposition was significantly increased in the calcified stained cells by cetylpyridinium chloride quantization, indicating that 3,5-DiCQA can promote the mineralization of MC3T3-E1 cells. Metabolomic analysis identified key metabolic changes, including the downregulation of phytosphingosine and upregulation of sphinganine and citric acid.DiscussionThese findings suggest that 3,5-DiCQA promotes osteoblast proliferation, differentiation and mineralization through pathways such as sphingolipid metabolism, arginine and proline metabolism, mucin type O-glycan biosynthesis and the citrate cycle (TCA cycle). This study provides insights into the therapeutic potential of 3,5-DiCQA for osteoporosis and highlights the utility of metabolomics in elucidating traditional Chinese medicine (TCM).